2016
DOI: 10.1159/000447308
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Simple Hepatic Cysts from Mucinous Cystic Neoplasms: Radiological Features, Cyst Fluid Tumour Marker Analysis and Multidisciplinary Team Outcomes

Abstract: Background: Differentiating hepatic mucinous cystic neoplasms (MCNs) from simple hepatic cysts (SCs) preoperatively is a challenging task. Our aim was to determine whether radiological features on ultrasound scan (USS), CT or MRI, cyst fluid tumour markers, or multidisciplinary team (MDT) outcomes could differentiate MCN from SC. Methods: A retrospective review of radiological features, cyst fluid tumour marker levels and MDT outcomes in 52 patients was performed. Results: There were 13 patients with MCN, 38 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 19 publications
0
33
0
Order By: Relevance
“…Major of H-MCNs occurred in women (20/29, 69%), particularly younger age women (≤ 60 year,79%), which is consistent with the previous study. [8,15] However, there were no significant differences in age and sex between H-MCNS and HSC, indicated that sex and age were not useful to distinguish these two diseases. Some patients of H-MCNs would complain about abdominal pain (14/29, 48.3%), fever (4/29,13.8%), jaundice (2/29,6.9%) and other symptoms, the symptom of fever was significantly higher than that of HSC, which could be explained that the H-MCNs originate from some congenitally aberrant bile ducts and could lead to cholangitis.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Major of H-MCNs occurred in women (20/29, 69%), particularly younger age women (≤ 60 year,79%), which is consistent with the previous study. [8,15] However, there were no significant differences in age and sex between H-MCNS and HSC, indicated that sex and age were not useful to distinguish these two diseases. Some patients of H-MCNs would complain about abdominal pain (14/29, 48.3%), fever (4/29,13.8%), jaundice (2/29,6.9%) and other symptoms, the symptom of fever was significantly higher than that of HSC, which could be explained that the H-MCNs originate from some congenitally aberrant bile ducts and could lead to cholangitis.…”
Section: Discussionmentioning
confidence: 97%
“…To improving the differential diagnosis between H-MCNs and HSC, some researchers make their effects on finding some statistical differences on markers. [8,11,15,16]. Due to a relatively rare quantity of H-MCNs, these small-sample studies can hardly find significant features to differentiate these two lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations